Cu(ii) complexes with tridentate sulfur and selenium ligands: catecholase and hydrolysis activity. (7th September 2020) - Durigon, Daniele Cocco; Maragno Peterle, Marcos; Bortoluzzi, Adailton João; Ribeiro, Ronny Rocha; Braga, Antonio Luiz; Peralta, Rosely Aparecida; Neves, Ademir
Abstract : Two new copper(ii ) mononuclear complexes (CSe and CS ) were synthesized and characterized by the following techniques: X-ray crystallography, elemental analysis, IR, EPR and UV-vis spectroscopies, conductimetric analysis and mass spectrometry. Abstract : Two new copper(ii ) mononuclear complexes (CSe and CS ) were synthesized and characterized by the following techniques: X-ray crystallography, elemental analysis, IR, EPR and UV-vis spectroscopies, conductimetric analysis and mass spectrometry. The crystalline structures of both complexes revealed two neutral complexes pentacoordinated with their chalcogenated ligands coordinating to the copper(ii ) center in a tridentate way with Se, N, Se and S, N, S as donor atoms and two cis -chloro ions completing the coordination structures. The hydrolytic activity in phosphate diester cleavage of CSe and CS was investigated using 2, 4-BDNPP as a substrate, and applying the Michealis–Menten approach, giving the kinetics parameters (CSe /CS ): k cat (s −1 ) = 1.17 × 10 −4 /1.97 × 10 −4 ; K M (mol L −1 ) = 3.13 × 10 −3 /5.58 × 10 −3 . Both complexes also catalyze the oxidation of the 3, 5-di- tert -butylcatechol (3, 5DTBC) substrate with turnover numbers of 4.32 × 10 −2 s −1 for CSe and 4.87 × 10 −2 for CS .